The Role of Core Capabilities in the Strategic Balance / An analytical Research in the Central Bank of Iraq - Hayder Mudhafar*, Noor Al-Hasan; Adel Hamed, Suhair (Journal of Economics and Administrative Sciences, 2024)
This research aims to investigate the relationship between two variables, namely core capabilities and strategic balance, within the context of the Central Bank of Iraq. The research problem emphasizes the necessity of implementing mechanisms that improve core capabilities to enhance strategic balance within the bank. the study highlights the importance of proposing various strategies to address the research problem, to achieve this, the research was conducted using a sample of 106 administrative leaders out of a total of 109, employing a purposive sampling method according to their positions and the organizational structure. The researcher used a descriptive-analytical approach and employed several statistical tools such as SPSS.V21, AMOSE, and Excel to analyze the relationship between the main research variables and answer the intellectual and applied questions, as well as examine the level of correlation and impact, Regression coefficient, correlation coefficient, mean, standard deviation, and variance were some of the statistical methods used, along with various diagrams and charts to illustrate the relationship between research variables and their sub-dimensions. These findings were then generalized to benefit the researched field, the primary data collection tools used were questionnaires, in addition to unstructured interviews and visits conducted within the Central Bank. The main and sub-hypotheses related to the correlation and impact relationships were tested to answer the research questions and achieve the study's objectives. The results indicated a significant and statistically meaningful influence of core capabilities on strategic balance. Based on these findings, it is recommended that the Central Bank prioritize investing in human resources to enhance strategic balance.